How vocal temporal parameters develop: a comparative study between humans and songbirds, two distantly related vocal learners. Issue 1 (27th November 2020) - Takahasi, Miki; Okanoya, Kazuo; Mazuka, Reiko
Abstract: Human infants acquire motor patterns for speech during the first several years of their lives. Sequential vocalizations such as human speech are complex behaviors, and the ability to learn new vocalizations is limited to only a few animal species. Vocalizations are generated through the coordination of three types of organs: namely, vocal, respiratory, and articulatory organs. Moreover, sophisticated temporal respiratory control might be necessary for sequential vocalization involving human speech. However, it remains unknown how coordination develops in human infants and if this developmental process is shared with other vocal learners. To answer these questions, we analyzed temporal parameters of sequential vocalizations during the first year in human infants and compared these developmental changes to song development in the Bengalese finch, another vocal learner. In human infants, early cry was also analyzed as an innate sequential vocalization. The following three temporal parameters of sequential vocalizations were measured: note duration (ND), inter-onset interval, and inter-note interval (INI). The results showed that both human infants and Bengalese finches had longer INIs than ND in the early phase. Gradually, the INI and ND converged to a similar range throughout development. While ND increased until 6 months of age in infants, the INI decreased up to 60 days posthatching in finches. Regarding infant cry, ND and INI were within similar ranges, but the INI was more stable in length than ND. In sequential vocalizations, temporal parameters developed early with subsequent articulatory stabilization in both vocal learners. However, this developmental change was accomplished in a species-specific manner. These findings could provide important insights into our understanding of the evolution of vocal learning.